The Last King of France’s Letters: The Controversy between Helen Maria Williams and Bertrand de Moleville about the Translation of Louis XVI’s Correspondence (ENTHYMEMA, 2023)
This article examines The Political and Confidential Correspondence of Lewis the Sixteenth (1803), by Helen Maria Williams, in which she translates the letters by Louis XVI while she adds her own political commentaries. This translation received negative reviews and one of its harshest critics was royalist emigré Bertrand de Moleville. The first part of this article explores the controversy that surrounded Correspondence and reveals that the letters were forged. The following part analyzes Williams’s political arguments that legitimize the deposition of Louis XVI as the king of France. The last part explores Bertrand’s Refutation, published in 1804. The article concludes that, regardless of the authenticity of the letters, Correspondence is a work that deserves reconsideration as it sheds light into Williams’s participation in the political debates of her time. Besides, the article shows that the misogynistic arguments employed by Bertrand contributed to the invisibilization of Williams’s work.
Keywords: Helen Maria Williams; French Revolution; translation; Bertrand de Moleville; Louis XVI